Tapping Into Actinobacterial Genomes for Natural Product Discovery - Singh, Tanim Arpit; Passari, Ajit Kumar; Jajoo, Anjana; Bhasin, Sheetal; Gupta, Vijai Kumar; Hashem, Abeer; Alqarawi, Abdulaziz A.; Abd_Allah, Elsayed Fathi (Frontiers in Microbiology, 2021)
The presence of secondary metabolite biosynthetic gene clusters makes actinobacteria well-known producers of diverse metabolites. These ubiquitous microbes are extensively exploited for their ability to synthesize diverse secondary metabolites. The extent of their ability to synthesize various molecules is yet to be evaluated. Current advancements in genome sequencing, metabolomics, and bioinformatics have provided a plethora of information about the mechanism of synthesis of these bioactive molecules. Accessing the biosynthetic gene cluster responsible for the production of metabolites has always been a challenging assignment. The genomic approach developments have opened a new gateway for examining and manipulating novel antibiotic gene clusters. These advancements have now developed a better understanding of actinobacterial physiology and their genetic regulation for the prolific production of natural products. These new approaches provide a unique opportunity to discover novel bioactive compounds that might replenish antibiotics' exhausted stock and counter the microbes' resistance crisis.